2019
DOI: 10.2196/humanfactors.9317
|View full text |Cite
|
Sign up to set email alerts
|

The Usability of Electronic Medical Record Systems Implemented in Sub-Saharan Africa: A Literature Review of the Evidence

Abstract: BackgroundElectronic medical record (EMR) systems hold the exciting promise of accurate, real-time access to patient health care data and great potential to improve the quality of patient care through decision support to clinicians. This review evaluated the usability of EMR systems implemented in sub-Saharan Africa based on a usability evaluation criterion developed by the Healthcare Information and Management Systems Society (HIMSS).ObjectiveThis review aimed to evaluate EMR system implementations in sub-Sah… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…The minimalist interface, ease of learning and use are the positive elements reported by users at the laboratory and ATC level that have facilitated its adoption. This is in agreement with Kavuma, which showed that ease of learning is the most important element in the adoption of electronic health record systems [15].…”
Section: Discussionsupporting
confidence: 91%
“…The minimalist interface, ease of learning and use are the positive elements reported by users at the laboratory and ATC level that have facilitated its adoption. This is in agreement with Kavuma, which showed that ease of learning is the most important element in the adoption of electronic health record systems [15].…”
Section: Discussionsupporting
confidence: 91%
“…Digitisation of health data then begins with the summary data upload to DHIS2 by HRIOs 33 34. The use of paper-based health information systems as a precursor to digital data capture is the norm in sub-Saharan African hospitals 26 35 36. Studies on DHIS2 specific to Kenya show it is ‘technically sound’ and can be successfully deployed and has improved data accessibility and completeness of reporting 37–39.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the assessment of the level of completion of the patient records, the low proportion recorded for emergency services (28%) could be explained by the increased frequentation by patients requiring emergency care, so the providers' concern would be focused on the provision of care rather than on the correct filling in of patient information. 13,14 Normally, computerization of the patient record should improve the completion of the record. However, some studies have identified problems with the completion and completeness of computerized patient records.…”
Section: Assessment Of the Level Of Completion Of The Electronic Patient Recordmentioning
confidence: 99%